Clinicopathological Study on Morphological Subtypes of Hepatocellular Carcinoma: A Single Tertiary Referral Center Experience - C. H. A. Saler; S. Shuai; J. C. Beckervordersandforth; D. Rennspiess; G. Roemen; T. Gevers; M. C. F. Stoehr‐Kleinegris; S. A. W. Bouwense; M. J. L. Dewulf; M. M. E. Coolsen; M. H. A. Bemelmans; S. W. Olde Damink; et al. (Cancer Reports, 2025)
ABSTRACT Aim We aimed to analyze hepatocellular carcinoma (HCC) morphological subtypes characterized according to the WHO classification and the International Collaboration on Cancer Reporting (ICCR) recommendations, and their prognostic features in a Dutch population. Methods and Results This retrospective study in a tertiary referral center included the histopathological revision of 62 HCC resection specimens, obtained from 22 female and 40 male patients (median age: 67 years), in a period between 2011 and 2021 at the Maastricht University Medical Center +. Clinical data, morphological subtypes, growth pattern (GP), tumor grade, tumor extension, margins, and vascular and perineural invasion were collected. Eighteen cases were assigned a specific morphologic subtype and steatohepatic HCC was the most common in our cohort. Twenty‐one tumors classified as conventional type HCC (HCC‐NOS), commonly exhibiting two concurrent GPs. Twenty‐three cases revealed a heterogeneous morphologic differentiation, compromising the combination of HCC‐NOS with another morphologic subtype, most frequently a steatohepatitic component. Comparison of HCC‐NOS and HCC with heterogeneous morphology did not show significant differences in the main clinicopathological characteristics and survival. Conclusion Although the most common morphologic subtype was steatohepatitic HCC, the majority of cases demonstrated multiple morphologic patterns. In case of HCC‐NOS, heterogeneous GPs were often observed. Therefore, a histomorphological diagnosis based on a single tumor biopsy specimen may lead to incorrect classification of HCC. Sufficient tumor sampling of HCC resection specimens is required for the complete evaluation of all histomorphological features followed by correct subclassification in order to meet the clinical needs regarding prognostic relevance and patient follow‐up.